Technology acceptance of a wearable collaborative augmented reality system in learning chemistry among junior high school students - Du, Juan (Duzce University, Faculty of Education, 2024)
Concepts related to molecular structure are often challenging for students to visualize and comprehend. Augmented reality has emerged as a promising solution to this problem, providing students with opportunities to manipulate and visualize chemical molecular structures to improve their understanding. Furthermore, collaborative learning environments have the potential to enhance student learning by fostering knowledge sharing and collaborative authoring. However, there is a dearth of research exploring students' acceptance of augmented reality in a collaborative learning context. Therefore, this study aims to investigate the technology acceptance of a wearable collaborative augmented reality system in chemistry education among junior high school students. Specifically, 124 students used Microsoft® HoloLens 2 device to learn about chemical molecular structure. Data was collected using the Extended Technology Acceptance Questionnaire after participants used the system and analyzed using Partial Least Squares Structural Equation Modeling. The extended model takes knowledge sharing, collaborating learning, and collaborative authoring as exogenous variables with perceived ease of use and perceived usability and finally produces a structural model that leads to behavioral usage intentions. The hypotheses tested in this study were accepted as the relationships were significant. Knowledge sharing, collaborative learning, and collaborative authoring have a positive impact on perceived usefulness and perceived ease of use respectively; and perceived usefulness and perceived ease of use have significant effects on behavioral intention to use respectively. This study conclusively demonstrated the hypothesized relationships. Evidence from these results provides comprehensive insights that can help policymakers and educators better understand the factors influencing the adoption of wearable collaborative augmented reality. © 2024, Duzce University, Faculty of Education. All rights reserved.